Physical biology of the cell - Phillips, Rob, 1960-; Kondev, Jane; Theriot, Jane; Garcia, Hernan G. (New York : Taylor & Francis Group, 2013)
'Physical Biology of the Cell maps the huge and complex landscape of cell and molecular biology from the distinct perspective of physical biology. As a key organizing principle, the proximity of topics is based on the physical concepts that unite a given set of biological phenomena. Herein lies the central premise: that the appropriate application of a few fundamental physical models can serve as the foundation of whole bodies of quantitative biological intuition, useful across a wide range of biological problems. The Second Edition features full-color illustrations throughout, two new chapters on the role of light in life and pattern formation, additional explorations of biological problems using computation, and significantly more end-of-chapter problems. This textbook is written for a first course in physical biology or biophysics for undergraduate or graduate students'--
Includes bibliographical references and index.
Keywords: Biophysics; Cytology; Cells; Cells -- Ultrastructure